The Effect of Place Attachment on Overseas Students’ Tourism Ambassador Behavior: A Mediation Role of Life Satisfactionrdrd - Wang, Xin; Lai, Ivan Ka Wai; Liu, Xinyu (Frontiers in Psychology, 2021)
Life satisfaction is a research hotspot in positive psychology in recent years. This study uses overseas students as subjects and attempts to examine the effect of place attachment and student life satisfaction on Mainland Chinese students’ word-of-mouth (WOM) recommendations and their Ambassador Behavioural (AB) intention. A survey was systematically conducted in six institutions in Macao. The results of 312 valid data indicate that place dependence has a positive influence on place identity; place identity and place dependence have a positive influence on student life satisfaction; student life satisfaction mediates the influence of the two dimensions of place attachment on WOM and AB intention. Recommendations are provided to improve overseas students’ life satisfaction in the study places. It helps to improve their sense of ownership and actively participate in the construction of the study places.